Social Changes on Basisombow in The Community of Kampar Riau Regency - Putri, Osmawinda; Hartono, Hartono; Utomo, Udi (Universitas Negeri Semarang, 2020)
Basisombow is a literature that develops in the North Kampar of Kampar District. In antiquity Basisombow was used for traditional event, wedding, and circumcision event. The research aims to describe and analyze the social change of Basisombow in the community of Kampar Riau Regency. This study used qualitative research, with a sociological approach. Observation technology, interviews and documentation are used as instruments of the research in collecting the data. The data analysis procedures used data reduction, data presentation and data verification. The validity of the data in this study used Triangulation source that was performed for the inspection process by examining data from multiple sources. The results of the study that Basisombow experienced social change as follows: 1). Changes on Kampar community structure; 2). new findings and other cultural contacts; 3). Differences of opinion amongst generations. In particular, the findings in social change are influenced by 2 (two) factors such as; external and internal factors which are related to the social environment of the Kampar community.